Identification of Protein Carbonyls (PCOs) in Canine Serum by Western Blot Technique and Preliminary Evaluation of PCO Concentration in Dogs With Systemic Inflammation - Ruggerone, Beatrice; Colombo, Graziano; Paltrinieri, Saverio (Frontiers in Veterinary Science, 2020)
In people, serum Protein Carbonyls (PCOs) increase during oxidative stress (OS) due to oxidative damage to proteins. OS is often associated with inflammation and especially with sepsis, a condition hard to diagnose in veterinary medicine because reliable markers are lacking. The aim of this study was to assess whether PCOs in canine serum may be detected by antibody-based methods such as Western Blotting (WB), and to preliminarily investigate the possible utility of this marker in dogs with inflammation. A serum sample oxidized in vitro was used to set up the method; the coefficient of variation obtained by repeated analysis varied from 24% to 36%. In order to assess whether the technique may cover the range of PCOs, concentration detectable in routine practice, PCOs were measured in 4 healthy dogs and in 14 with inflammatory diseases, in some cases potentially associated with sepsis, as suggested by the results other inflammatory markers such as C-Reactive Protein (CRP) and the anti-oxidant enzyme Paraoxonase-1 (PON-1)): the concentration of PCOs was low in dogs with normal PON-1 activity, moderately increased in the majority of dogs with low-normal PON-1 activity, and severely increased in dogs with very low PON-1 activity. In conclusion, this study demonstrates that PCOs may be detected in canine serum, using antibody-based techniques such as WB. The preliminary results in dogs with and without systemic inflammation encourage further studies on the possible role of PCOs as inflammatory markers.